2013
DOI: 10.1016/j.juro.2013.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Patients with Metastasis to the Prostatic Anterior Fat Pad Lymph Nodes: A Multi-Institutional Study

Abstract: Most patients with prostatic anterior fat pad metastatic disease had intermediate to high risk features preoperatively. In some patients with such lymph node metastasis removing these lymph nodes resulted in prolonged biochemical recurrence-free survival. Therefore, we recommend that the prostatic anterior fat pad be removed in all patients undergoing radical prostatectomy. However, pathological analysis of the prostatic anterior fat pad may be limited to patients with intermediate to high risk oncological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…The risk might be different with extended PLND as studies have shown that staging accuracy depends on the extent of the anatomical template used, but higher complication rates are more likely [15,[35][36][37][38]. The number or percentage of +LNs seems to be more important for determining outcomes, although increasing LN yield may result in improved survival rates by removing micrometastatic nodal tissue [11,13,21,[39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk might be different with extended PLND as studies have shown that staging accuracy depends on the extent of the anatomical template used, but higher complication rates are more likely [15,[35][36][37][38]. The number or percentage of +LNs seems to be more important for determining outcomes, although increasing LN yield may result in improved survival rates by removing micrometastatic nodal tissue [11,13,21,[39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…AFP tissue is usually formally mobilized during robot-assisted RPs, to help define the prostate apex and prostate/bladder junction, but is not routinely submitted for pathological assessment [51]. Published series have shown that LNs can be identified in 5.5-16.7% of AFP tissue with a 0.9-2.5% incidence rate of metastases [45,[52][53][54][55]. In the present study, four patients were upstaged to N1 disease as a result of isolated AFP LN metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, 40.0% of all patients (203/500) received NVB preservation, whereas only 18.2% (44/242) of high-risk patients received NVB preservation. Another explanation is that we performed BPLND in the majority of cases (94.2%), including pre-prostate fat pad dissection for all patients and extended BPLND for high-risk patients 1047…”
Section: Discussionmentioning
confidence: 99%
“…The fibro‐fatty tissue anterior to the prostate (PAFP) is often removed during RP to improve precision during the apical dissection. Recently, several authors, summarised in Table , have demonstrated that this tissue contains LN tissue draining from the prostate.…”
Section: Discussionmentioning
confidence: 99%